2013
DOI: 10.1007/s12105-013-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Analogue Secretory Carcinoma of Salivary Gland Origin: An Update and Expanded Morphologic and Immunohistochemical Spectrum of Recently Described Entity

Abstract: Mammary analogue secretory carcinoma of salivary gland origin (MASC) is a recently described tumor with ETV6 translocation. Akin to secretory breast cancer, MASC expresses S-100 protein, mammaglobin, vimentin, and harbors a t(12;15) (p13;q25) translocation which leads to ETV6-NTRK3 fusion product. Histologically, MASC displays a lobulated growth pattern and is often composed of microcystic, tubular, and solid structures with abundant eosinophilic homogeneous or bubbly secretions. Colloidlike secretory material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 26 publications
7
126
0
Order By: Relevance
“…S100 staining was seen in 11/31 ACCs but appeared much weaker and restricted compared to MASCs. This is in agreement with previous reports showing that diffuse and strong S100 expression may distinguish MASCs from ACCs [1,7]. Mammaglobin and S100 have also been suggested as proxy markers for MASC [22].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…S100 staining was seen in 11/31 ACCs but appeared much weaker and restricted compared to MASCs. This is in agreement with previous reports showing that diffuse and strong S100 expression may distinguish MASCs from ACCs [1,7]. Mammaglobin and S100 have also been suggested as proxy markers for MASC [22].…”
supporting
confidence: 93%
“…However, this study investigated nineteen cases of MASC, but included only one ACC making the staining specificity somewhat uncertain. One suggested criterion is that S100 expression must be strong and diffuse [7], but others have shown that S100 can be variably expressed in ACC and other tumours may show strong diffuse expression [8]. The correct diagnosis may have implications with respect to clinical behaviour and the presence of a specific chromosomal translocation offers a potential target for future biological therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, multiple authors have described some patterns found in MASC as appearing similar to thyroid colloid-like deposition or a follicular pattern of thyroid carcinoma [1,3,7,17]. Nuclear features of our patient's tumor also resembled closely those of PTC in that the nuclei were vesicular with numerous nuclear grooves.…”
Section: Discussionsupporting
confidence: 67%
“…1 The recurrent t(12;15) (p13;q25) rearrangement results in the fusion of ETV6, a transcriptional regulator on 12p13, with NTRK3, which encodes a membrane tyrosine kinase receptor. 12,13 This same ETV6/NTRK3 fusion is also characteristic of secretory carcinoma of the breast, a tumor that is histologically identical to MASC, as well as congenital mesoblastic nephroma, congenital fibrosarcoma, and some forms of acute myeloid leukemia. 6 Subsequent reports of MASC broadened the histologic range of this neoplasm, as macrocystic, polypoid, and papillocystic patterns and perineural invasion were described.…”
Section: Discussionmentioning
confidence: 98%